PENGARUH JUMLAH PASIEN DALAM RUANG RAWAT INAP KELAS VIP DAN KELAS III TERHADAP JUMLAH KOLONI BAKTERI PADA GAGANG PINTU DAN GAGANG TEMPAT TIDUR PASIEN DI SALAH SATU RUMAH SAKIT DI KOTA MALANG - Silvia Candra Devy (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2018)
Introduction: Southeast Asia has a high prevalence of 10%. Indonesia has a prevalence of 7.1% that can increased morbidity and mortality. There are theories about bed occupancy can impact on bacterial transmission, where door handles and bed rail are the highest transmission. This study aims to see whether the number of patients can affect the number of bacterial colonies on door handle and bed rail of patient.Methods: This research is in vitro study, using a post-test observational analytical design by comparing the number of bacteria colonis in the door handles and bed rail of patient with the number of patient. Sample has been taken with swab by steril cotton swab in door handle and bed rail. The bacteria in the samples were inoculated on NA, BAP, and MacConkey media to determine the number of bacterial colonies. Culture is done for 24 hours.Results: There were no significant differences between the number of bacterial colonies in the door handle and bed rail of the VIP and class III room (P>0.05). The number of patients did not correlate with the number of bacterial colonies in the door handle and bed rail (P>0.05) .The most commonly found bacteria is Staphylococcus spp.Conclusion : There is no difference between of number colonies in door handle and bed rail and there is no effect of bed occupancy on the of the number colonies